Consumption Experience and Sales Promotion Expenditure - Fornell, Claes; Robinson, William T.; Wernerfelt, Birger (Management Science, 1985)
An economic theory of habit formation through consumption learning is developed to explain order differences in relative sales promotion expenditures among brands. The theory applies to consumer brands in equilibrium markets, where consumer information from sources other than advertising, sales promotion, and previous consumption experience is negligible. Three propositions are derived from the theory: brands with more consumption experience (1) spend proportionately less on sales promotion as well as (2) on advertising and promotion combined, and (3) place proportionately more emphasis on advertising relative to sales promotion. These propositions are formulated as hypotheses and tested against empirical data from the PIMS project. It is found that the data are generally consistent with the propositions. In order to examine the robustness of the results, the hypotheses are subjected to three different empirical tests, each with different assumptions. The findings are shown to be reasonably robust with respect to these changes in assumptions.